Optimizing Myanmar’s community-delivered malaria volunteer model: a qualitative study of stakeholders’ perspectives - Win Han Oo; Elizabeth Hoban; Lisa Gold; Kyu Kyu Than; Thazin La; Aung Thi; Freya J. I. Fowkes (Malaria Journal, 2021)
Abstract Background In parallel with the change of malaria policy from control to elimination and declines in the malaria burden in Greater Mekong Sub-region, the motivation and social role of malaria volunteers has declined. To address this public health problem, in Myanmar, the role and responsibilities of malaria volunteers have been transformed into integrated community malaria volunteers (ICMV), that includes the integration of activities for five additional diseases (dengue, lymphatic filariasis, tuberculosis, HIV/AIDS and leprosy) into their current activities. However, this transformation was not evidence-based and did not consider inputs of different stakeholders. Therefore, qualitative stakeholder consultations were performed to optimize future malaria volunteer models in Myanmar. Methods Semi-structured interviews were conducted with key health stakeholders from the Myanmar Ministry of Health and Sports (MoHS) and malaria implementing partners to obtain their perspectives on community-delivered malaria models. A qualitative descriptive approach was used to explore the experiences of the stakeholders in policymaking and programme implementation. Interview topic guides were used during the interviews and inductive thematic data analysis was performed. Results While ICMVs successfully provided malaria services in the community, the stakeholders considered the ICMV model as not optimal and suggested that many aspects needed to be improved including better training, supervision, support, and basic health staff’s recognition for ICMVs. Stakeholders believe that the upgraded ICMV model could contribute significantly to achieving malaria elimination and universal health care in Myanmar. Discussion and conclusion In the context of high community demand for non-malaria treatment services from volunteers, the integrated volunteer service package must be developed carefully in order to make it effective in malaria elimination programme and to contribute in Myanmar’s pathway to universal health coverage (UHC), but without harming the community. An evidenced-based, community-delivered and preferred model, that is also accepted by the MoHS, is yet to be developed to effectively contribute to achieving malaria elimination and UHC goals in Myanmar by 2030.